Associação de paclitaxel e irinotecano como estratégia de modulação de suas toxicidades, neuropatia periférica e mucosite intestinal em camundongos - Torquato, Bruna Bezerra (2023)
One of the biggest challenges with the use of antineoplastic agents match the toxic effects on the individual's normal cells. One of the most common adverse effects of irinotecan, a topoisomerase 1 inhibitor, is damage to the gastrointestinal tract. On the other hand, paclitaxel, a mitotic inhibitor taxane, damages nerve cells at neuronal, ganglionic and medullary levels. Studies show that Irinotecan and Paclitaxel act, respectively, as toll-like receptor type 4 (TLR4) antagonist and agonist, impacting the development of their respectively toxicities. Thus, considering the opposite role of these drugs on TLR4 receptors, the present study aimed to verify whether the combination of these chemotherapy drugs would attenuate the development of their toxicities, namely, intestinal mucositis and peripheral neuropathy (PN). For this, tests were carried out with male C57BL/6 mice, weighing between 18 and 22 grams and divided into 4 groups (n=6/group) and following the following treatment scheme: Group 1: Control (vehicle, NaCl 0 .9%, i.p); Group 2: Paclitaxel (PTX, 8 mg/kg, i.p. days: 0, 2, 4 and 6); Group 3: Irinotecan (IRI, 75 mg/kg, i.p. days: 1, 2, 3 and 4); Group 4: Paclitaxel + Irinotecan (PTX, 8 mg/kg, i.p. days: 0, 2, 4 e 6 + IRI, 75 mg/kg, i.p. days: 1, 2, 3 e 4). The following tests were performed to assess mucositis: weight assessment, assessment of the degree of diarrhea, bowel length total leukocyte count and to assess peripheral neuropathy, von Frey filament tests and TLR4 and ATF3 expression were performed by immunofluorescence in dorsal root ganglia and spinal cord. The protocol was approved by the animal ethics committee of the Federal University of Ceará (CEUA/UFC n° 8664300919). The results showed that in relation to mucositis there was an increase in diarrhea in the animals treated with IRI, as well as the animals in the PTX+IRI group. There was also a decrease in the total number of leukocytes, especially neutrophils, in animals from the PTX, IRI and PTX+IRI groups. A decrease in bowel size was observed in animals treated with IRI and especially in animals treated with PTX+IRI. The presence of diarrhea was also observed in the IRI and PTX+IRI groups. In relation to NP, the animals in the PTX+IRI group had a reduction in plantar sensitivity in the von Frey test, compared to the PTX group. Immunofluorescence assays for ATF3 (marker of neuronal damage) observed that the expression of this transcription factor was reduced in the PTX+IRI group compared to PTX, while immunofluorescence for TLR4 increased in the dorsal root ganglion in the PTX+IRI group versus the IRI group. We conclude that the association between paclitaxel and irinotecan was not able to reverse mucositis, however the combination of the two antineoplastic agents was beneficial in attenuating NSP, without impacting the survival rate of the animals.